EMISI CO2 DAN STRATEGI INDUSTRI 4.0: ANALISIS PADA INDUSTRI CRUDE PALM OIL INDONESIA - Rizki Maulana Prasetyo; Novi Mela Yuliani; Risna Amalia Hamzah; Nina Rahmawati; Slamet Alfian (Jurnal Bina Bangsa Ekonomika, 2023)
The palm oil industry is one of the leading commodities and one of the main export players in Indonesia. This industry also contributes to Indonesia's Gross Domestic Product (GDP) of 3.5% - 4%. Based on data from the Central Bureau of Statistics in 2023, the number of palm oil companies has increased dynamically in the last 20 years, this raises a trade off, namely whether the growth of the palm oil industry can harm the environment? Or can the growth of the palm oil industry increase its contribution to Indonesia's GDP share? The purpose of this study is to predict in the short term over 10 periods how the influence of the number of CPO companies and international CPO Prices on Indonesia's carbon emissions and GDP growth. The method used in this study is using quantitative methods using the Vector Autoregression (VAR) model to test the Criteria of Lag and the Vector Error Correction Model (VECM) to see the impulse graph. The results show that the increase in CPO companies will contribute positively to variable CO2 emissions, while if Indonesian CPO companies increase it will increase international CPO prices. This can encourage Indonesia's CPO production as one of Indonesia's main export commodities which in turn the increase in exports can increase Indonesia's GDP